1985
DOI: 10.1515/botm.1985.28.4.133
|View full text |Cite
|
Sign up to set email alerts
|

“Haemagglutinins” of the Phaeophyceae and Non-specific Aggregation Phenomena by Polyphenols

Abstract: The nature of the human erythrocyte "agglutinins" in six selected species of brown algae has been investigated. The "haemagglutinins" are removed by the incorporation of insoluble polyvinylpolypyrrolidone (PVPP) into the extraction medium and cannot be recovered from the PVPP by elution with media containing Tween 80. Protein-rich extracts from the six algae do not contain "agglutinins' 1 for human erythrocytes, but purified polyphenols from four of the six species produce powerful "haemagglutination". Thus th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1989
1989
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Rogers and Loveless (1985) and Blunden et al (1986) have shown that extracts of brown algae, including that of A. nodosum, no longer 'agglutinate' erythrocytes if polyphenols are removed from the extracts with insoluble PVPP. Fabregas et al (1986) have made similar observations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rogers and Loveless (1985) and Blunden et al (1986) have shown that extracts of brown algae, including that of A. nodosum, no longer 'agglutinate' erythrocytes if polyphenols are removed from the extracts with insoluble PVPP. Fabregas et al (1986) have made similar observations.…”
Section: Resultsmentioning
confidence: 99%
“…However, this work by Rogers and Loveless (1985) did not entirely resolve the situation as the possibility remained that true lectins had been removed from the brown algal extracts along with the polyphenols, due to non-specific binding of the lectins by the polyphenols.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Indeed, the polyphenols may be expected to inhibit most enzymes and react with most other proteins (Loomis, 1974). The non-dialysable polyphenols from A. nodosum and some other brown algae have been shown to cause nonspecific aggregation of human erythrocytes (Rogers & Loveless, 1985;Blunden et al, 1986), presumably because one polyphenol molecule can react with protein at the cell surface of several erythrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, HA was more due to the polyphenols content of the P. minor that was co-extracted with the lectins than the P. minor lectin. According to Rogers and Loveless (1985), polyphenols were reported to have strong HA. However, lectin HA is based on the specific interaction of lectin with the erythrocytes' The false hemagglutinating capacity of polyphenols might become a concern for research on lectin of brown algae (Cortés-giraldo et al, 2012) which resulted in the small number of the Phaeophyta lectin researches.…”
Section: Resultsmentioning
confidence: 99%